Dismantling Gender Specificity and Establishing Women’s Space/Voice: A Womanist Study of Alice Walker’s The Third Life of Grange Copeland - Jesmin, UH Ruhina; Buly, Farhana Osman (Spectrum, 2022)
The paper is a womanist study based on African-American novelist Alice Walker’s 1970 novel, The Third Life of Grange Copeland. The study uses content analysis method, Walker’s theory of womanism, and Judith Butler’s theory of undoing gender performativity to explore how Walker’s women characters dismantle gender specificity and establish women’s space/voice. Walker’s women characters perceive womanism as a defensive strategy and a healing force as they find it self-healing in restoring their mental health, self-respect, and identity. They do not believe in separation from their male partners; they stand victorious over the racist-sexist society by taking men as partners and by taking their own decisions regarding life and death. Womanism, as their philosophy of life, allows them space for raising voice, forming identity, uplifting status, and finding wholeness of their lives accompanied by men. Their womanist identities reflect a conscious/subversive act of transfiguring differentiation and give them a vision of women’s space, a sense of hidden possibilities, and a sense of wholeness. They exercise their sexual freedom which poses a threat to the ideological and political basis of male supremacy. Their womanist performativity questions heteronormativities and stimulates social change. As such, their womanist identities speak more of a political preference than a mere sexual/non-sexual preference. The study explores how Ruth idealizes her womanist foremothers as her role models and takes her grandfather as her partner. She creates women’s space/possibilities, weaves her future, and journeys towards wholeness. In fact, she defines herself as one of those possibilities which womanism opens up. Spectrum, Volume 16, June 2021: 148-158